(untitled) (Research, Society and Development, 2021)
Objective: Investigate the prevalence of the use of antidepressant meds among healthcare students in Brazil and, the factors that contribute to the maintenance of this habit. Methodology: This is an interactive literature review, looking for articles in the databases indexed in PubMed and in the Virtual Health Library (VHL), including: LILACS, MEDLINE and BDENF. After analyzing, by a inclusion and exclusion method, a sample of 7 articles was selected. Results And Discussion: Most studies reveal a relevant data about the number of students in the healthcare area who use antidepressants meds, the Selective Serotonin Reuptake Inhibitors (SSRI) being the most used. Besides, is pointed out that the huge workload, family distance, difficulty to making new friends and the reduced time for leisure are reasons for the use of these medications. Conclusion: Because of this important prevalence of the use of antidepressant medications by university students in the healthcare area in Brazil, is inferred the need of develop preventive measures in order to minimize the impacts caused by high levels of stress and prevent the development of depressive symptoms.